Basic radiological physics - Thayalan, Kuppusamy (Jaypee, 2017)
The revised edition incorporates the entire syllabus of BSc (AHS) course of radiology and imaging technology (RIT), radiotherapy technology (RTT) and MSc (medical physics) of Indian universities.